(untitled) (Conferencea, 2023)
In this thesis, the influence of urbanization and ecological processes of Fergana region on crime is studied. Different forms of crime in cities and towns of the region and the connection of such crimes with the process of urbanization are analyzed. The thesis drew on field research, scientific literature, articles, and statistical data analysis, as well as some of the authors’ sociological research to determine the relationship between urbanization and crime.